Polymyxin derivatives as broad-spectrum antibiotic agents. Issue 87 (15th October 2019) - Su, Ma; Wang, Minghui; Hong, Yuzhu; Nimmagadda, Alekhya; Shen, Ning; Shi, Yan; Gao, Ruixuan; Zhang, En; Cao, Chuanhai; Cai, Jianfeng
Abstract : A few polymyxin derivatives with broad-spectrum antimicrobial activity were developed. Lead compound P1 disrupted bacterial membranes rapidly without developing resistance. Abstract : We designed a few polymyxin derivatives which exhibit broad-spectrum antimicrobial activity. Lead compound P1 could disrupt bacterial membranes rapidly without developing resistance, inhibit biofilms formed by E. coli, and exhibit excellent in vivo activity in an MRSA-infected thigh burden mouse model.